EMT-INDUCED ACTIN CYTOSKELETAL REORGANIZATION: IMPLICATIONS FOR CANCER CELL MIGRATION - Marat, Iliyas (Nazarbayev University School of Sciences and Humanities, 2025)
Epithelial-to-mesenchymal transition (EMT) is a feature of cellular plasticity that occurs during normal physiological processes, such as embryogenesis and organ development, as well as in pathological conditions such as cancer metastasis. There is a need for detailed studies that specifically focus on EMT in cancer cells, as the process may occur to varying degrees depending on the origin. In addition, the behavior of cancer cells during the different phases of EMT remains underexplored. A substantial number of publications have focused on the prolonged induction of EMT in vitro for 72 h, whereas the behavior of cells during early EMT requires further investigation. Therefore, this study aimed to analyze the changes in morphology, transcriptomics, actin cytoskeleton, and motility of post-EMT A549 adenocarcinoma cells. Specifically, these characteristics were studied at the early and late stages of EMT in cells after 24 and 72 h of incubation with TGFβ-1 (5 ng/mL). The results showed that A–549 cells continuously changed their morphology during EMT. After 24 h of EMT induction, the cells became elongated and spindled. After 72 h of EMT induction, the cells acquired a fibroblast-like morphology. The actin cytoskeleton of post-EMT cells was transformed into stress fibers, and this effect was more prominent after late EMT stimulation. The most significant result was observed for cell motility after the EMT. Post-EMT cells after 12-24 h of induction had a significantly higher capacity for migration than post-EMT cells after 72 h of induction. Prolonged induction of EMT using TGFβ-1 (5 ng/mL) leads to the differentiation of cells into fibroblast-like cells that exhibit reduced cell motility. In light of the extent of actin stress fiber formation and changes in the morphology of post-EMT cells, it was concluded that TGFβ-1 induced EMT results in distinct motility changes in cells at the early and late stages of EMT.
Keywords: epithelial-to-mesenchymal transition; cancer; gene expression; actin cytoskeleton; cell migration; cell invasion; metastasis; type of access: embargo